Aging process analysis of LiNi0.88Co0.09Al0.03O2/graphite–SiOx pouch cell. (1st October 2018) - Wang, Lve; Zhang, Bin; Pang, Jing; Liu, Yuan; Wang, Xi; Chang, Zenghua; Lu, Shigang
Abstract: Nickel-rich layered oxide and graphite–SiOx are regarded as promising electrode materials for high energy density lithium ion cells. It is significant to illustrate the degradation mechanism related to the aging process of nickel-rich layered oxide cathode and graphite–SiOx anode in full cell. In this study, the as-prepared pouch cell with LiNi0.88 Co0.09 Al0.03 O2 as cathode material and graphite–SiOx as anode material has been proved with three aging stages according to the capacity retention changes in behavior. The aging process of the pouch cell is studied by non-destructive electrochemical methods. And then the pouch cells at different aging stages are disassembled and the cell components are studied by electrochemical characterizations for reassembled electrodes and physico-chemical analysis techniques. In the result, the cathode degradation is slight and as a minor factor for the degradation of the whole cell, and the anode deterioration is worse and as the main factor for the degradation of the whole cell. The organic and inorganic composition changes of the solid electrolyte interphase (SEI) induce the aging behavior differences of the three stages, and the reversible lithium loss, electrochemical polarization and active material shedding are mainly responsible for the three stages, respectively. Highlights: As-prepared LiNi0.88 Co0.09 Al0.03 O2 /graphite–SiOx pouch cell has three aging stages. Both non-destructive and post-mortem methods are used to illustrate the aging stages. The organic and inorganic composition changes of SEI induce the aging behavior differences. The lithium loss, polarization and active material shedding are the three main factors.